Geometric morphometrics for the differentiation of females of the Pipiens Assemblage in Argentina - Garzón, Maximiliano Javier (2020)
Complexes or assemblages of culicid species and subspecies from the southern region of Latin America are difficult to differentiate morphologically (Harbach 2012, Laurito et al. 2017). These complexes include taxa with differences in their vectorial capacity and therefore in their epidemiological importance (Dujardin and Schofield 2004). However, morphological variation within the species and superposition of diagnostic characters based on classical structures often do not allow for a correct identification. The aim of this work was to evaluate, through geometric morphometry, differences in the wing shape of female mosquitoes belonging to the Pipiens Assemblage (Cx. pipiens and Cx. quinquefasciatus) of Argentina.